The Narrative Thread: Weaving a Tapestry of Meaning in John Locke's An Essay Concerning Human Understanding - Simmons, Patricia Catherine (My University, 1996)
Richard Rorty's seminal work, Philosophy and the Mirror of Nature (1979), a text that critiques the foundationalist aspirations of philosophy, locates John Locke within a line of thinkers primarily concerned with discerning and accurately representing either the external "reality" of the world or the internal essence of human beings. Such thinkers, according to Rorty, have perpetuated the conception of philosophy as foundational-that is, mediating between "reality" and all other claims to knowledge in order to adjudicate accuracy of representation. Contending that the conception of philosophy as foundational derives from an obsolete vocabulary inherited from the seventeenth century, Rorty locates philosophic texts on par with all other texts, whose relation to the world is functional rather than foundational. Rorty then proposes that philosophy assume a more pragmatic cultural role as the promoter, but not the arbiter, of more fruitful redescriptions of ourselves to deal with the historically specific complexity of the world. Rorty's conception of language as a tool that underpins his argument that texts bear a functional as opposed to foundational relation to the world forms the theoretical framework for my analysis of John Locke's An Essay concerning Human Understanding. Although the putative impetus of Locke's Essay is discerning the origin of our ideas as the foundations of all knowledge, this thesis proffers an alternate reading of Locke's Essay by attending to its rhetorical structure. More specifically, I argue that the Essay is an experiential and experimental text that insistently involves the reader in the textual exegesis of mind. Based on my reading of the rhetorical movements and literal denotation of the Essay, I propose that the primary aim of the text was not to represent accurately the cognitive processes of the mind forming ideas about the world as the foundations of all knowledge; rather, I suggest that the Essay self-consciously functions metaphorically by proffering a new vocabulary with which to think about mind, world, language, and society as a viable alternative to endless sectarian strife. Using Rorty's vocabulary to redescribe Locke's rhetorical project in the Essay, I suggest that Locke's text not only embodies an awareness of its own contingency, but functions within its historical context in the role which Rorty proposes for philosophy. In this regard, Locke and Rorty become aligned on an imaginative continuum in their shared rhetorical project of redescription with specifically pragmatic aims.
Keywords: critiques, foundationalist, philosophy, 'reality', language, vocabulary